2016
DOI: 10.5772/62251
|View full text |Cite
|
Sign up to set email alerts
|

Formyl-Peptide Receptor Agonists and Amorphous SiO2-NPs Synergistically and Selectively Increase the Inflammatory Responses of Human Monocytes and PMNs

Abstract: We tested whether amorphous SiO2-NPs and formylpeptide receptor (FPRs) agonists synergistically activate human monocytes and neutrophil polymorphonuclear granulocytes (PMNs). Peptide ligands specifically binding to FPR1 (f-MLP) and to FPR2 (MMK-1, WKYMVM and WKYMVm) human isoforms did not modify the association of SiO2-NPs to both cell types or their cytotoxic effects. Similarly, the extent of CD80, CD86, CD83, ICAM-1 and MHCII expression in monocytes treated with SiO2-NPs was not significantly altered by any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In fact, formyl peptide receptor agonists have been shown to synergize cytokine production by monocytes and the chemotactic response in PMNGs in the presence of SiO 2 NPs. However, no upregulation of maturation markers like that which was shown to occur in DCs was induced in these cells (39). No data on the possible up-modulation of costimulatory markers in macrophages under the conditions used in this study are currently available.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In fact, formyl peptide receptor agonists have been shown to synergize cytokine production by monocytes and the chemotactic response in PMNGs in the presence of SiO 2 NPs. However, no upregulation of maturation markers like that which was shown to occur in DCs was induced in these cells (39). No data on the possible up-modulation of costimulatory markers in macrophages under the conditions used in this study are currently available.…”
Section: Discussionmentioning
confidence: 64%
“…Such a possibility is indeed suggested by the little evidence that is available: endocytosed NPs and the lipopolysaccharide (LPS) of Gram-negative bacteria synergistically increase the levels of cytokine production by monocytes, macrophages, and DCs (17,(31)(32)(33)(34)(35)(36) and cytotoxicity in A549 epithelial cells (37). In addition, prokaryotic agonists of formyl peptide receptors (FPRs) synergize with different NP types [SiO 2 NPs, bare or pegylated organically modified silica NPs, poly(lactic-coglycolic acid) NPs, and liposomes] in determining specific inflammatory responses in monocytes and PMNs (38,39).…”
mentioning
confidence: 99%
“… 59 The increased IL-8 expression is induced primarily via activation of PAMP receptors such as TLRs and FPRs. 36 , 60 However, cytokines and other molecules associated with inflammation are also potent stimulators of IL-8 expression. 61 , 62 The production of cytokines by immune cells exposed to bacteriocins is poorly understood; the published reports are mostly focused on nisin, but some of them are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…MMK-1, an FPR2 agonist, is by far the more commonly used peptide, and studies have shown that it may be useful as an anti-anxiety drug, as well as a drug to counteract hair loss from chemotherapy [98,104]. However, there has been some concern about its use in certain drug regimens, as it may amplify the response of monocytes to SIO 2 -coated nanoparticles, making it an important player in calculating the proper dosing when using such nanoparticles [105]. MMWLL is another M-peptide specific for FPR1.…”
Section: Synthetic Peptides and Non-peptide Small Moleculesmentioning
confidence: 99%